2003
DOI: 10.1152/japplphysiol.00764.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of surface-tension-induced epithelial cell damage in a model of pulmonary airway reopening

Abstract: Airway collapse and reopening due to mechanical ventilation exerts mechanical stress on airway walls and injures surfactant-compromised lungs. The reopening of a collapsed airway was modeled experimentally and computationally by the progression of a semi-infinite bubble in a narrow fluid-occluded channel. The extent of injury caused by bubble progression to pulmonary epithelial cells lining the channel was evaluated. Counterintuitively, cell damage increased with decreasing opening velocity. The presence of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
346
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(375 citation statements)
references
References 52 publications
20
346
0
5
Order By: Relevance
“…We have also found that for Ca Ω < 10Ca M the bubble tip pressure drop ΔP tip may be estimated accurately from the pressure measured downstream of the bubble tip when corrections for the pressure drop due to Poiseuille flow are applied. The normal stress gradient at the tube wall (∂τ n /∂z) is discussed in detail, as this is believed to be the primary factor in airway epithelial cell damage (Bilek et al 2003). In the unsteady regime we find that local film-thinning produces high ∂τ n /∂z at low Ca Ω .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…We have also found that for Ca Ω < 10Ca M the bubble tip pressure drop ΔP tip may be estimated accurately from the pressure measured downstream of the bubble tip when corrections for the pressure drop due to Poiseuille flow are applied. The normal stress gradient at the tube wall (∂τ n /∂z) is discussed in detail, as this is believed to be the primary factor in airway epithelial cell damage (Bilek et al 2003). In the unsteady regime we find that local film-thinning produces high ∂τ n /∂z at low Ca Ω .…”
Section: Introductionmentioning
confidence: 78%
“…Bilek et al (2003) demonstrated that an increased normal stress gradient ∂τ n /∂z along a channel wall is directly correlated to increased cell mortality. Those studies focused on very small values of Ca (2.7 × 10 −5 ≤ Ca ≤ 6.8 × 10 −4 ), and showed that a decrease in Ca resulted in an increase in ∂τ n /∂z (corresponding to increased cell damage).…”
Section: Normal Stress Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the cell membrane of the pulmonary epithelial cells could be disrupted by the steep pressure gradient appearing during airway reopening [3,6]. Furthermore, cytoskeletal damage in vitro was demonstrated after the impact of 16 MPa (120000 mmHg) on a human renal carcinoma cell line [4].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to suspect that the pressure changes may influence the vital function of the cell. According the recent studies, pressure fluctuations can induce cell membrane disruption, cytoskeleton disorganization and enzymes inactivation [2][3][4][5][6]. There are also some evidences about the pressure induced fragmentation of DNA isolated from cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%